Meta-Synthesis of Health Behavior Change Meta-Analyses - Johnson, Blair T. (American Public Health Association, 2010)
Objectives. We integrated and compared meta-analytic findings across diverse behavioral interventions to characterize how well they have achieved change in health behavior. Methods. Outcomes from 62 meta-analyses of interventions for change in health behavior were quantitatively synthesized, including 1011 primary-level investigations with 599 559 participants. Content coding suggested 6 behavioral domains: eating and physical activity, sexual behavior, addictive behaviors, stress management, female-specific screening and intervention behaviors, and behaviors involving use of health services. Results. Behavior change interventions were efficacious (mean effect sizes = 0.08–0.45). Behavior change was more evident in more recent meta-analyses; those that sampled older interventions and literatures or sampled more published articles; those that included studies that relied on self-report, used briefer interventions, or sampled fewer, older, or female participants; and in some domains (e.g., stress management) more than others (e.g., sexual behaviors). Conclusions. Interventions improved health-related behaviors; however, efficacy varied as a function of participant and intervention characteristics. This meta-synthesis provides information about the efficacy of behavioral change interventions across health domains and populations; this knowledge can inform the design and development of public health interventions and future meta-analyses of these studies.